The relationship between adolescents’ digital gaming behaviors and parenting behaviors - Canoğlu, Büşra; Doğan, Aysun (Journal of Dependence, 2025)
In today’s world, children and adolescents often spend their free time playing digital games, driven by technological advancements. Adolescents, in particular, are more inclined towards digital gaming due to the changes they experience during this developmental stage. This review study aims to explore the relationship between adolescents’ digital gaming behaviors and parental influence, considering the potential risks associated with digital gaming. To achieve this, research conducted from 2000 onwards was reviewed. The literature indicates that adolescents’ gaming behaviors are influenced by parental behavioral control and parenting styles. Consequently, this study examines parenting behaviors in terms of attitudes and control. The findings suggest that adolescents whose gaming behaviors are monitored by their parents, and those with parents who adopt an explanatory authoritarian style, are less likely to engage in excessive digital gaming. Future research should investigate various risk factors, particularly parental attitudes, styles, and behaviors, that contribute to adolescents’ digital gaming, and develop preventive intervention programs based on these factors.